Signatures of the Arctic Stratospheric Ozone in Northern Hadley Circulation Extent and Subtropical Precipitation. Issue 21 (5th November 2019) - Hu, Dingzhu; Guan, Zhaoyong; Tian, Wenshou
Abstract: Previous studies showed that Antarctic ozone could modulate the Hadley circulation (HC) and precipitation in the Southern Hemisphere. However, whether and how, if any, Arctic stratospheric ozone (ASO) modulates the northern HC and subtropical precipitation remains unclear. We found an out‐of‐phase relationship between the northern HC extent (HCE) and ASO during boreal spring on interannual timescales during 1979–2014. Decreased (increased) ASO tends to result in an equatorward (poleward) shift of HCE by +0.67° (−0.45°) latitude per one standard deviation of decreased (increased) ASO year. Observational analysis and model simulations show that increased ASO leads to an equatorward shift of HCE and subtropical moistening via weakened eddy momentum flux and decreased subtropical static stability, accompanied with negative eddy momentum flux divergence anomalies and northward meridional wind anomalies over the subtropics. Our results may help to understand the linkage between the Arctic and midlatitudes, especially important for the subtropical precipitation and hydrological cycle. Plain Language Summary: The loss of Antarctic ozone and its impacts on midlatitude troposphere including subtropical jet and precipitation in the Southern Hemisphere have been paid attention by scientists, policymakers, and the public in recent years. The subtropical dry zone and precipitation are determined by the Hadley circulation (HC); however, whether and how, if any, Arctic stratospheric ozone (ASO) modulates the HC and subtropical precipitation in the Northern Hemisphere (NH) remains unclear. Here, we found that the decreased (increased) ASO tends to result in an equatorward (poleward) shift of the HC extent, further moistening (drying) the subtropics by modifying eddy momentum flux divergence and static stability over the subtropics. These results suggest the midlatitude climate anomalies in the NH may be modulated by the Arctic stratosphere, which is important for the subtropical precipitation and hydrological cycle. Key Points: The northern HCE is anticorrelated with the Arctic stratospheric ozone on interannual timescales Depletion of Arctic ozone tends to result in an equatorward shift of the HCE The equatorward shifted HCE related to Arctic stratospheric ozone depletion may moisten the subtropics in the NH